Ujęcie reprezentacji i reklamy w ustawach o podatku VAT - Tatarska, Marzena (Depiction of Representation and Promotion in the Acts Concerning the Value Added Tax, 2005)
The most important change concerning representation and promotion introduced by the new value added tax act of May l 2004 are presented in the article. The most essential problems connected with this issue are described there.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 125-136